Commercial Video Games As Therapy: A New Research Agenda to Unlock the Potential of a Global Pastime - Colder Carras, Michelle; Van Rooij, Antonius J.; Spruijt-Metz, Donna; Kvedar, Joseph; Griffiths, Mark D.; Carabas, Yorghos; Labrique, Alain (Frontiers in Psychiatry, 2018)
Emerging research suggests that commercial, off-the-shelf video games have potential applications in preventive and therapeutic medicine. Despite these promising findings, systematic efforts to characterize and better understand this potential have not been undertaken. Serious academic study of the therapeutic potential of commercial video games faces several challenges, including a lack of standard terminology, rapidly changing technology, societal attitudes toward video games, and understanding and accounting for complex interactions between individual, social and cultural health determinants. As a vehicle to launch a new interdisciplinary research agenda, the present paper provides background information on the use of commercial video games for the prevention, treatment and rehabilitation of mental and other health conditions, and discusses ongoing grassroots efforts by online communities to use video games for healing and recovery.